Shea waste slurry as an organic soil amendment of tropical soils in the Tamale Metropolis, Northern Ghana - Abagale F. K.; Alazuga I. N. A; Osei A. R. (African Journal of Pig Farming, 2022)
Infertile and less productive soil due to continuous cropping, poor soil management and other forms of land exploitation are mostly amended using inorganic fertiliser. Shea waste slurry (SWS) as an organic soil amendment material was applied to soils in two locations and its effect on plant primary and secondary nutrients evaluated. One-way diagonal method was employed in sampling soil from fields measuring 25 m×40 m at depths of 0-30 and 30-60 cm for SWS applied and non-applied soils. Results showed increased pH resulting from SWS application and EC increasing from 41.15±3.89 to 155.5±83.4 µS/cm in both locations. SWS application also increased %N levels at depth of 0-30 cm from 0.03±0.0 to 0.56±0.2%, concentration of P increased from 3.47±0.62 to 262.0±176 mg/kg and K from 21.9±2.39 to 231.6±98 mg/kg. Na levels increased from a low of 0.46±0.09 to a maximum of 2.81±1.0 meq/100 g in both study sites, Mg increased from 0.80±0.3 to 8.51±4.86 meq/100 g whilst Ca increased from 1.6±0.07 to 6.3±098 meq/100 g for the depth of 0-30 cm. Soil %OM and OC, respectively increased from 0.58±0.01 to 10.94±3.95 and 0.34±0.11 to 6.36 ±2.29% for the depth of 0 to 30 cm in both study locations. The study indicated a general increase in the levels of all the parameters analysed for the study at the SWS applied soils as compared to the non-applied soils. The use of SWS as a soil nutrient amendment in crop production as an organic material was observed to be very effective.